Multi-pathway oxidative stress amplification via controllably targeted nanomaterials for photoimmunotherapy of tumors - Song Li; Yunheng Liu; Xiaokang Zhang; Yurong Liu; Longqing Si; Shaojing Jiang; Aoya Wang; Xukai Che; Jing Chen; Jinghui Hu (Journal of Nanobiotechnology)
Abstract Photoimmunotherapy, which combines phototherapy with immunotherapy, exhibits significantly improved therapeutic effects compared with mono-treatment regimens. However, its use is associated with drawbacks, such as insufficient reactive oxygen species (ROS) production and uneven photosensitizer distribution. To address these issues, we developed a controllable, targeted nanosystem that enhances oxidative stress through multiple pathways, achieving synergistic photothermal, photodynamic, and immunotherapy effects for tumor treatment. These nanoparticles (D/I@HST NPs) accurately target overexpressed transferrin receptors (TfRs) on the surface of tumor cells through surface-modified transferrin (Tf). After endocytosis, D/I@HST NPs generate ROS under 808-nm laser irradiation, breaking the ROS-responsive crosslinking agent and increasing drug release and utilization. Tf also carries Fe3+, which is reduced to Fe2+ by iron reductase in the acidic tumor microenvironment (TME). Consequently, the endoperoxide bridge structure in dihydroartemisinin is cleaved, causing additional ROS generation. Furthermore, the released IR-780 exerts both photodynamic and photothermal effects, enhancing tumor cell death. This multi-pathway oxidative stress amplification and photothermal effect can trigger immunogenic cell death in tumors, promoting the release of relevant antigens and damage-associated molecular patterns, thereby increasing dendritic cell maturation and sensitivity of tumor cells to immunotherapy. Mature dendritic cells transmit signals to T cells, increasing T cells infiltration and activation, facilitating tumor growth inhibition and the suppression of lung metastasis. Furthermore, the myeloid-derived suppressor cells in the tumor decreases significantly after treatment. In summary, this multi-pathway oxidative stress-amplified targeted nanosystem effectively inhibits tumors, reverses the immunosuppressive tumor microenvironment, and provides new insights into tumor immunotherapy combined with phototherapy.